COVID-19 Vaccination and Pregnancy - Natalia Ignaszak-Kaus; Karolina Chmaj-Wierzchowska; Katarzyna Wszołek; Maciej Wilczak (Clinical and Experimental Obstetrics & Gynecology)
Objectives: A review to assess the safety, efficacy, COVID-19 vaccination acceptance and awareness in pregnant women. Machanism: Pregnant women diagnosed with COVID-19 are characterized by more frequent hospitalization in intensive care units and are at three times higher risk of preterm; their newborns more often need invasive ventilation. Vaccination is the most effective preventive measures against SARS-CoV-2, but there are still questions about safety and immune response. Pregnant women were not included in study groups during phase III clinical trials. Findings in Brief: Vaccination during pregnancy is not associated with an increased risk of obstetric or neonatal complications; scientific communities recommend vaccination for pregnant women, those planning for pregnancy and those who are breastfeeding. Unfortunately, knowledge regarding COVID-19 vaccination and willingness to take vaccine during pregnancy is low. Conclusions: General practitioners and obstetricians have a large role in increasing public awareness of COVID-19 vaccination. No evidence of teratogenicity of the vaccine has been found.